2003
DOI: 10.1074/jbc.m304307200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transcription Factor Stat5 Induces Cell Death of Human Prostate Cancer Cells

Abstract: Identifying regulators of prostate cancer cell survival may lead to new therapeutic strategies for prostate cancer. We now report prevalent activation of transcription factor Stat5 in human prostate cancer and provide novel evidence that blocking activation of Stat5 in human prostate cancer cells leads to extensive cell death. Specifically, Stat5 was activated in 65% of human prostate cancer specimens examined based on nuclear location of tyrosine phosphorylated Stat5. Adenoviral gene delivery of a dominant-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
142
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 26 publications
14
142
0
Order By: Relevance
“…Its activation in the prostate cancer correlates with high Gleason grade. 33,34 We and others demonstrated STAT3 phosphorylation in LNCaP cells in which growth was inhibited by IL-6 and found that 22Rv1 cells stimulated by IL-6 do not exhibit any phosphorylation of STAT3. 6,29,35 As noted by Clevenger, 13 the role of STAT3 is in breast cancer, similar to that in prostate cancer, incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Its activation in the prostate cancer correlates with high Gleason grade. 33,34 We and others demonstrated STAT3 phosphorylation in LNCaP cells in which growth was inhibited by IL-6 and found that 22Rv1 cells stimulated by IL-6 do not exhibit any phosphorylation of STAT3. 6,29,35 As noted by Clevenger, 13 the role of STAT3 is in breast cancer, similar to that in prostate cancer, incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DN forms of STAT5A or STAT5B has previously been shown to affect the survival of various cell types (Mui et al, 1996;Dumon et al, 1999;Lord et al, 2000;Ahonen et al, 2003). In addition, deletion of stat5 genes in mouse can also disturb the survival and maturation of myeloid and erythroid progenitors cultured in the presence of granulocytemacrophage colony-stimulating-factor and erythropoietin (Socolovsky et al, 1999;Kieslinger et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…BCR-ABL tyrosine kinase inhibitors can block STAT5 signaling 48 with consequent growth arrest and induction of apoptosis. Tommi et al 49 showed that STAT5 is activated in human prostate cancer cells. Inhibiting STAT5 leads to prostate cancer cell apoptosis.…”
Section: Evasion Of Programmed Cell Deathmentioning
confidence: 99%